HUBUNGAN DUKUNGAN SAUDARA KANDUNG DENGAN KOMUNIKASI INTERPERSONAL PADA ANAK AUTIS DI PUSAT LAYANAN AUTIS KOTA DENPASAR - Widyandari, Ni Made Ayu Sukma; Puspita, Luh Mira; Sanjiwani, Ida Arimurti (Coping: Community of Publishing in Nursing; Vol 10 No 6 (2022): Desember 2022, 2022)
An interpersonal communication disorder is one of the problems experienced by children with autism. It causes due to the lack of development of language skills so children with autism have difficulty delivering and receiving messages from others. One of the factors that influence the development of communication in children with autism is sibling support. This study aims to determine the correlation of sibling support with interpersonal communication in children with autism at Pusat Layanan Autis Kota Denpasar. This research uses descriptive correlation design with the cross-sectional approach. The sample consisted of 38 children selected by total sampling technique based on the affordable population criteria. Data collection using sibling support questionnaires and Interpersonal Communication Inventory (ICI) questionnaires. The result showed that the mean of sibling support for autistic children was 22,76 and the mean of interpersonal communication in autistic children was 18,18. Data tested using Spearman Rank (rho) got a significant value of 0,00 (? = 0,05) with a correlation value of 0,794 and positive direction correlation. This shows a strong correlation with a positive direction which means the better support siblings the better interpersonal communication to the children with autism.